Unsupervised method for normalization of hematoxylin-eosin stain in histological images - Azevedo Tosta, Thaina A.; Faria, Paulo Rogerio de; Silva Servato, Joao Paulo; Neves, Leandro Alves [UNESP]; Roberto, Guilherme Freire; Martins, Alessandro Santana; Nascimento, Marcelo Zanchetta do (Elsevier B.V., 2019)
Histological images stained with hematoxylin-eosin are widely used by pathologists for cancer diagnosis. However, these images can have color variations that highly influence the histological image processing techniques. To deal with this potential limitation, normalization methods are useful for color correction. In this paper, a histological image color normalization is presented by considering the biological and hematoxylin-eosin properties. To this end, the stain representation of a reference image was applied in place of the original images representation, allowing the preservation of histological structures. This proposal was evaluated on histological images with great variations of contrast, and both visual and quantitative analyzes yielded promising results. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Histopathological image analysis; Normalization; Spectral matching; Sparse non-negative matrix factorization